Kinetic evaluation of sewage sludge treatment by membrane anaerobic system (MAS) - Bee Tin, Chew (2012)
The application of Membrane Anaerobic System (MAS) process treating the sewage sludge and the overall MAS treatment efficiency was investigated.The MAS consists of a cross flow ultrafiltration membrane (Model Micro 240) for solid-liquid separation. Six parameters were investigated.The study showed a good trend for the Membrane Anaerobic System (MAS) treating raw sewage sludge.The removal efficiency of Chemical Oxygen Demand (COD) was 80 to 95 %, the removal efficiency of Total Suspended Solid (TSS) was 99 % and Volatile Suspended Solid (VSS) removal efficiency was 82 to 93 %. Throughout the study,the pH values were maintained from7.5 to 7.8.The gas production ranged from 7200 ml/d to 16320 ml/d. The percentage of the methane gas production was found to be 75.4 %.The treated sewage sludge was achieved the environmental standard quality.